KOMPETENSI TENAGA KEPENDIDIKAN DI MTSN 1 BONE - P, MULIATI; HAFID, ERWIN; YUSPIANI, YUSPIANI (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
Human resources in streamlining school administration are very important, and cannot be separated from one component to another. Therefore, administrative staff who are skilled, reliable and understand the job description are very necessary. The lack and low competence of school administration staff is a phenomenon that needs to be resolved immediately. This research was conducted at MTsN 1 Bone with the aim of knowing the personality competence, social competence, technical competence and managerial competence of education staff at MTsN 1 Bone. The research results show that: 1) The personality competencies of education staff at MTsN 1 Bone include integrity and noble character, flexibility and discipline; 2) The social competence of education staff at MTsN 1 Bone includes providing excellent service and ensuring effective communication; 3) The technical competence of educational staff at MTsN 1 Bone includes administering personnel administration by administering the division of tasks, and administering personnel by administering the division of tasks; 4) The managerial competence of education staff at MTsN 1 Bone includes preparing work programs and reports, creating a conducive work climate, and optimizing resource utilization. ABSTRAKSumber daya manusia di dalam memperlancar tata administrasi sekolah sangatlah penting, serta tidak bisa dipisahkan antara komponen yang satu dengan yang lain. Maka dari itu sangat diperlukan tenaga tata administrasi yang terampil, handal, serta paham akan job diskripsinya. Masih kurang dan rendahnya kompetensi yang dimiliki tenaga tata administrasi sekolah menjadi sebuah fenomena yang perlu dituntaskan dengan segera. Penelitian ini dilakukan di MTsN 1 Bone dengan tujuan mengetahui kompetensi kepribadian, kompetensi sosial, kompetensi teknis, dan kompetensi manajerial tenaga kependidikan di MTsN 1 Bone. Hasil penelitian menunjukkan bahwa: 1) Kompetensi kepribadian tenaga kependidikan di MTsN 1 Bone meliputi integritas dan akhlak mulia, fleksibel, dan disiplin; 2) Kompetensi sosial tenaga kependidikan di MTsN 1 Bone meliputi, memberikan layanan prima, dan memastikan komunikasi efektif; 3) Kompetensi teknis tenaga kependidikan di MTsN 1 Bone meliputi melaksanakan administrasi kepegawaian dengan terorganisir dalam pembagian tugas, dan administrasi kepegawaian dengan terorganisir dalam pembagian tugas; 4) Kompetensi manajerial tenaga kependidikan di MTsN 1 Bone meliputi menyusun program dan laporan kerja, menciptakan iklim kerja kondusif, dan mengoptimalkan pemanfaatan sumber daya.